The value of five blood markers in differentiating mycosis fungoides and Sézary syndrome: a validation cohort. (1st August 2021) - Dobos, G.; De Cevins, C.; Ly Ka So, S.; Jean‐Louis, F.; Mathieu, S.; Ram‐Wolff, C.; Resche‐Rigon, M.; Bensussan, A.; Bagot, M.; Michel, L.
Summary: Background: Clinical and histological diagnosis of Sézary syndrome (SS) and mycosis fungoides (MF) is challenging in clinical routine. Objectives: We investigated five blood markers previously described for SS (T‐plastin, Twist, KIR3DL2, NKp46 and Tox) in a prospective validation cohort of patients. Methods: We included 447 patients in this study and 107 patients were followed up for prognosis. The markers were analysed by reverse transcriptase quantitative real‐time polymerase chain reaction (RT‐qPCR) on peripheral blood leucocytes and CD4 + T cells in a cohort of consecutive patients with early MF, erythrodermic MF and SS and compared with patients presenting with benign inflammatory dermatoses (BID) and erythrodermic BID. The markers were assessed in parallel to gold standard values such as CD4/CD8 ratio, loss of CD7 and CD26 membrane expression and CD4 absolute values. Sensitivity and specificity were analysed by receiver operator characteristic curves. The prognostic value of selected markers was analysed on a subset of patients. This study was conducted in one centre. Results: We defined cut‐off values for each marker. T‐plastin, Twist and KIR3DL2 had the best validity. SS may be overrepresented. The combination of T‐plastin and Twist was able to differentiate between erythrodermic MF or BID and SS. The additional analysis of KIR3DL2 may be useful to predict the prognosis. Conclusions: We propose T‐plastin, Twist and KIR3DL2 measured by RT‐qPCR as new diagnostic markers for Sézary syndrome.